Exit taxation in relation to cross-border mergers - Sára Budínská; Jana Skálová (European Financial and Accounting Journal, 2024)
The article looks at exit taxation within the European Union, including how it affects cross-border mergers. It starts with an explanation of the concept of exit tax, followed by an analysis of the current legislation and an analysis of the case law of the European Court of Justice. The article presents the results of the research, the implementation of exit taxes in a particular country, including how it is calculated, the determination of the market and tax value and the tax rate. The second objective is to examine how the rule is applied to cross-border mergers. The data was obtained through a qualitative data collection method in the form of a questionnaire survey from December 2023 to January 2024. The Baker Tilly Group's advisory network was selected to obtain high quality information. The questionnaire was sent to the employees of this company at the highest management positions who are responsible for tax advisory. The results of the survey showed that all countries analysed have implemented exit tax according to the rules set by the EU and mostly apply this tax to cross-border mergers. However, the application to mergers is not uniform and an assessment is needed for each case implemented as to whether it will be exempt from the exit tax.
Keywords: G34; H25; K34; 650; ATAD; Cross-Border Mergers; Exit Taxation